E-Learning-Based Learning Innovation: Students' Engagement In The Digital Era - Khotimah, Khusnul; Hilmawan, Ginan; M. A, Roidhotun (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
E-learning-based learning innovation has become one of the main solutions in improving student engagement in the digital era. This article aims to explore the various forms of student engagement in e-learning and its impact on learning outcomes. Through the literature review method, it examines relevant studies in the past five years, which show that student engagement can be divided into several categories, including cognitive, emotional, social, and practical engagement. The results show that high engagement in e-learning is positively associated with improved learning outcomes, motivation, and development of students' social skills. In addition, e-learning also promotes learning independence, which is important for future learning. The findings emphasize the importance of designing interactive and engaging e-learning experiences to increase student engagement, thus supporting educational success in the digital era